Hubungan jabatan, masa kerja dan dukungan keluarga dengan motivasi perawat untuk melanjutkan pendidikan Ke jenjang sarjana keperawatan - Ratmanita - -; Veny - Elita; Wasisto - Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The is study aims to determine the relationship between position, period of employment and family support with the motivation to continue their study to undergraduate level. This study uses the description of correlation with cross-sectional. The number of sample is 62 respondents drawn using random sampling techniques. Instrument used was a questionnaire with 20 statements. The analysis method uses the chi-square statistical test with a significance level of p <α (0.05). The statistical test result obtains p value for positions is 0.349, p value of years 0.090, and family support p value = 0.709 > α = 0.05, it can be concluded that there is no significant relationship between position, period of employment, and family support with the motivation to continue their education to undergraduate level. It is Expected the nurses should seek to increase knowledge and skills through formal and non-formal education, in order to achieve improve their qualities to provide nursing services. Keywords : Family support, Position, period of employment, motivation, nursing education, nurse